Kepemilikan Lukisan Digital yang Dihasilkan AI dalam Perspektif Hak Cipta - Panjaitan, Theograce Ulibasa; Taruno M, Yudho (Indonesian Publication Center, 2026)
In Indonesia, copyright protection is governed by Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta. This law serves as the legal foundation for the regulation, protection, and enforcement of the rights of creators. Copyright protection cannot be separated from the continuous evolution of technology, as digital transformation has given rise to Artificial Intelligence (AI). AI is capable of creating a work of art merely by receiving an instruction and compiling data, thereby enabling it to imitate original works that have previously been protected by copyright. This raises questions regarding the ownership status of works generated by AI. This research aims to analyze and determine the ownership of a painting created by AI. The type of research employed is normative juridical with a prescriptive nature, utilizing statutory and conceptual approaches. The results of the study indicate that the ownership status of AI-based works is determined by the level of creativity of the prompt creator as well as the outcome of the Substantial Similarity Test to assess whether there is any infringement upon works that have been protected. This research underscores the necessity for more adaptive regulations in order to provide legal certainty in response to the development of AI technology.